The use of the smartphone for the management of collaborative work in argentine higher education students during the COVID-19 pandemic - Albarello, Francisco Javier (2021)
The situation of mandatory social isolation due to the global COVID-19 pandemic has affected all walks of life, and education has not been the exception. Not only have universities adapted to the new landscape by offering virtual teaching instances, but students have developed collaborative study practices using Smartphones and other digital devices. This article presents the results of a qualitative research that included in-depth interviews with 45 Argentine university students, to investigate the changes that the quarantine has generated in their ways of studying. The findings indicate that students develop complex collaborative study strategies, alternating between texts, audios, and other materials and applications that allow them to study and compensate for the physical absence of their classmates through collaborative work mediated by screens.